(untitled) (Research, Society and Development, 2020)
Viral hepatitis are diseases caused by different etiologic agents (HAV, HBV, HCV, HDV AND HEV), with primary tropism for the hepatic tissue, presenting similar epidemiological, clinical and laboratory characteristics, but with important particularities. The present study aimed to characterize the epidemiological profile of viral hepatitis in the Brazilian scenario. It was a documentary, retrospective, descriptive research with a quantitative approach. The notified cases of viral hepatitis were collected from the Department of Informatics of the Unified Health System (DATASUS) with the variables studied: year, region, sex, clinical form and etiological classification of the notified cases. Between 2014-2018, 216,397 cases of viral hepatitis were reported in Brazil. Of these notified cases, 40% correspond to the southeast region and, to a lesser extent, 7% correspond to the central-west region. Analyzing the cases of hepatitis by year of notification, the following percentage distribution was obtained: 2014 (22%), 2015 (21%), 2016 (20%), 2017 (19%), 2018 (18%). There was no very discrepant difference in relation to male (56%) and female (44%). Regarding the final classification, the cases consisted predominantly of laboratory confirmation (98%). The predominant clinical form was chronic hepatitis / carrier (77%). Regarding the etiological classification, the HCV virus prevailed over the cases (50%). The epidemiological study made it possible to understand the aspects and distribution of viral hepatitis in Brazil. In addition, it was an initiative to carry out further investigations as well as the notification and monitoring of these cases, in order to expand knowledge about the prevalence of viral hepatitis in the Brazilian scenario.